DamBuster Uma ferramenta de avaliação de soluções de mitigação de DoS volumétrico direto - Silva, Eduardo Sousa da; Lopes, Paulo Mauricio Costa; Gondim, João José Costa (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2023: Companion Proceedings of the 23rd Brazilian Symposium on Information and Computational Systems Security, 2023)
DamBuster is a dual application tool for studying volumetric attacks and also evaluating and benchmarking mitigation systems for volumetric direct denial of service flooding attacks, implemented in a modular architecture. The tool implements attacks abusing various protocols, under customized conduction tactics and controlled intensity. Application performance is analyzed by comparing the results of available attacks, running on different hardware configurations and against a commonly used reference tool (T50). The results show that DamBuster is a scalable and efficient tool for packet injection and traffic generation. The average packet generation and forwarding rates obtained were higher and more consistent than those of the T50.